Continuously declining incidence of hip fracture in Finland: Analysis of nationwide database in 1970–2016. (July 2018) - Kannus, Pekka; Niemi, Seppo; Parkkari, Jari; Sievänen, Harri
Highlights: Hip fractures are a major public health issue. The age-adjusted incidence of hip fracture rose sharply in older Finns from 1970s till the end of 1990s but has declined thereafter. The only way to limit the rise in fracture numbers is to have further decline in fracture incidence. Abstract: Background: Hip fractures of older adults are a major public health issue. Methods: We determined the current trend in the number and incidence (per 100, 000 persons) of hip fracture among older adults in Finland by taking into account all persons 50 years of age or older who were admitted to hospitals for primary treatment of such fracture between 1970 and 2016. Results: The number of hip fractures rose sharply till the end of 1990s (from 1857 in 1970 to 7122 in 1997), but since then, the rise has slowed down (7716 fractures in 2016). Similarly, the age-adjusted incidence of hip fracture increased until 1997 but declined thereafter. The decline was especially clear in women whose age-adjusted incidence was 537.9 (per 100, 000 persons) in 1997 but only 344.1 in 2016. In men, the corresponding incidence was 256.5 in 1997 and 194.7 in 2016. With the current 2016 incidence rates, the number of hip fractures in Finland will increase by 44% by the year 2030 due to the sharp growth of the population at risk. The only way to limit the rise is to have a further decline in fracture incidence in 2016–2030. Conclusions: The decline in the incidence of hip fracture in Finland has continued through the entire new millennium. Despite this we have to effectively continue implementation of the fracture prevention efforts, because our elderly population will grow rapidly in the near future.